Prevalence of complementary alternative medicine use among patients with type II diabetes in Negeri Sembilan, Malaysia - Baharom N,; Shamsul Azhar Shah,; Rotina AB, (Faculty of Medicine, Universiti Kebangsaan Malaysia, 2016)
The uses of Complementary and Alternative Medicine (CAM) among patients with chronic diseases are becoming increasingly popular. This was a descriptive cross-sectional study conducted in 45 government health clinics across Negeri Sembilan. Respondents at diabetes clinics were selected via systematic random sampling and interviewed using structured questionnaire. CAM usage was divided into three groups; CAM use for diabetes (CAM-DM), CAM use for general health (CAM-G) and Non CAM user. The prevalent use of CAM among type II diabetes mellitus patients in Negeri Sembilan was 58.5% (CAM-DM: 40.6% and CAM-G: 17.9%). For CAM-DM group, bitter gourd (Momordica charantia) was the most popular CAM consumed to help control diabetes, while supplement milk was the most popular choice for the CAM-G group. In conclusion, the use of CAM among type II diabetes mellitus patients in Negeri Sembilan was common. Natural products are the main choice of CAM modality used to help with the management of diabetes. Majority of CAM users never informed their healthcare providers about their CAM use.